(untitled) (Altre Modernità, 2016)
In the early 1930s the crime film Scarface: The Shame of a Nation (1932, USA, dir. Howard Hawks) stirred censorship controversies in the United States because of its gritty portrayal of criminality and violence. Debates over crime, race and immigration proliferated in the North-American press and finally led to Italian-American pressure groups to call out for the film’s boycott because it ‘offended the Italian nation and people’ and vilified immigrant communities. Archival historical research in AVT has revealed how film versions have frequently been cut and dialogues ideologically manipulated to suit political agendas, commercial interests and dominant sexual and religious moralities. Indeed the translation of films has often served too many masters, suffering direct or indirect censorship intervention whenever a film defied existing societal taboos. My contribution aims to offer a diachronic perspective on the reception of Scarface lo sfregiato in Italy. It will look at the film’s Italian-language translation and re-translations for cinema, television and DVD, prepared by different hands and re-voiced by different actors during a span of fifty years (1940-90s). From the textual and contextual analysis of the film’s different Italian editions, it will be possible to trace significant ideological shifts in the reception of Italian-American crime iconography and in the language used to communicate it.